Digital Symmetrical Peripheral Gangrene: A Rare Male PresentAtion of AntiPhospholipid Anti Body Syndrome (Journal of Dhaka Medical College, 2016)
Anti-phospholipid antibody syndrome can be defined as the occurrence of venous and arterial thrombosis with or without recurrent miscarriage in association with laboratory evidence of persistent Antiphospholipid antibody / antibody to beta-2-Glycoprotein-1 / anti cardiolipin antibody /lupus anticoagulant (usually associated with SLE). It occurs usually in female who can present with recurrent miscarriage and fetal loss. Anti-phospholipid Antibody can be also found in some autoimmune diseases and post viral infections. Even certain drugs; e.g. phenothiazine, can cause it. Arterial thrombosis may lead to peripheral limb ischemia, stroke, and myocardial infarct. And venous thrombosis may be found in the form of DVT, pulmonary embolism & thrombosis in vessels supplying the abdominal organ.J Dhaka Medical College, Vol. 24, No.2, October, 2015, Page 152-155